Clown care in the clinical nursing of children: a meta-analysis and systematic review - Wang, Lina; Zhu, Jing; Chen, Ting (Frontiers in Pediatrics, 2024)
Background Children treated in hospitals often experience high levels of anxiety and pain. The purpose of this meta-analysis was to analyze the effect of clown care in clinical nursing on children and to provide ideas for improving the clinical nursing care provided to children. Methods Two authors searched PubMed, Embase, Clinical trials, Cochrane Library, Web of Science, CINAHL, Scopus, China National Knowledge Infrastructure (CNKI), Weipu, and Wanfang databases to identify randomized controlled trials (RCTs) related to clown care for children until 15 September 2023. The quality assessment of the included RCTs and the data extraction were performed by two researchers, and meta-analysis was carried out using RevMan5.4. Results A total of 15 RCTs involving 2,252 children were finally included in this meta-analysis. The findings from this meta-analysis revealed that clown care was beneficial in reducing the pain [SMD = −0.96, 95% CI (−1.76, 0.16)], anxiety [SMD = −0.81, 95% CI (−1.16, −0.46)], and crying time [SMD = −1.09, 95% CI (−1.74, −0.44)] of children and the anxiety level of caregivers [SMD = −0.99, 95% CI (−1.95, −0.03)] (all P’s < 0.05). No significant publication biases were detected in the synthesized outcomes (all P’s > 0.05). Conclusions Clown care is helpful in reducing the pain, anxiety, and crying time of children and the anxiety level of caregivers. However, additional high-quality studies with larger sample sizes are warranted to further analyze the role of clown care in clinical practice.